Nondirected Pd-catalyzed aerobic C-H alkenylation of ruthenocene and ferrocene - Mueller, Sven; Lee, Woohyeong; Song, Jae Yeong; Kang, Eunsu; Joo, Jung Min (Chemical Communications, 2022)
Pd-catalyzed alkenylations of metallocenes via C-H activation were developed using electronically tunable pyrazolonaphthyridine (PzNPy) ligands. Ferrocene was alkenylated using the most electron-deficient ligand in the series, whereas the less reactive ruthenocene needed balancing of the electrophilicity and stability of catalysts. Various alkenes were installed, allowing fine-tuning of redox potentials.
CRIS-Team WoS Importer:2022-09-16